The lost husband [videorecording (DVD)] - Wight, Vicky; Bibb, Leslie; Duhamel, Josh, 1972-; Dunn, Nora, 1952-; Lawrence, Sharon, 1961-; Center, Katherine (Quiver Distribution, 2019)
Trying to put her life back together after the death of her husband, Libby and her children move to her estranged Aunt's goat farm in central Texas.